Effect of intraoperative irrigation with alteplase on adhesion formation associated with intraperitoneal chemotherapy (experimental study) - Meydanli, M. M.; Celik, H.; Hanay, F.; Nalbant, M. (I R O G Canada, Inc, 2008)
Objective: To examine the efficacy of intraoperative irrigation with alteplase, a tissue plasminogen activator, for the prevention of adhesion formation associated with intraperitoneal chemotherapy. Material and Methods: Rats, in which serosal injury was induced in the right uterine horn and ipsilateral parietal peritoneum, were randomly divided into four groups. Group I (n = 10) had intraoperative intraperitoneal irrigation with alteplase following the standard operation. Group 11 (n = 10) had irrigation with normal saline, while the rats in Group III (n = 10) and Group IV received no peritoneal irrigation. All rats, except for those in Group IV, received intraperitoneal (IP) paclitaxel plus carboplatin chemotherapy on the seventh postoperative day, and all rats were sacrificed seven days after chemotherapy. Total adhesion scores in the induced standard defects were calculated by evaluating percentage of adhesion formation, as well as the severity and degree of the adhesions. The scores were compared among the groups. Results: Comparison of the severity, percentage, degree and total score of adhesions among the groups demonstrated that subjects in Group 1, where intraoperative alteplase irrigation was used, had fewer adhesion components (severity, percentage, degree) and a lower total adhesion score when compared to the other groups (p < 0.05). Adhesion components and the total adhesion score in Group IV, which did not receive chemotherapy, were found to be significantly lower when compared to Groups 11 and III (p < 0.05). Conclusion: Intraoperative Alteplase irrigation may reduce adhesion formation associated with intraperitoneal chemotherapy. Thus, intraperitoncal chemotherapeutic agents may be ensured to reach all peritoneal surfaces easily.
Keywords: intraperitoneal chemotherapy; adhesion formation; paclitaxel; carboplatin; alteplase